Recurrent Glioblastoma Resection with Microvascular Free Flap Reconstruction and Associated GammaTile Implantation: A Personalized Approach with Oncologic and Reconstructive Integration - Wagner, Russel T.; Berardinelli, Jacopo; Kassam, Amin B.; Bailes, Julian E.; Fukui, Melanie B.; Bobustuc, George C.; Khalili, Sammy; Mundi, Neil S. (Journal of Neurological Surgery Reports, 2025)
Glioblastoma multiforme (GBM), despite aggressive multimodal treatment comprising surgery followed by chemoradiation, is almost uniformly associated with inevitable recurrence and poor outcomes. In this clinical context, local radiation therapy—an emerging approach—has gained considerable attention over time for its potential to address the limitations of traditional treatment options for GBM. Multiple surgeries and adjuvant chemoradiation therapy can negatively impact the integrity of the scalp soft tissues and can compromise the ability to achieve primary closure over the surgical site. In these circumstances, complex reconstruction with free tissue transfer may be necessary.We report the case of a 37-year-old female patient with recurrent GBM and associated wound healing complications who underwent single-stage GammaTile surgically targeted radiation therapy combined with microvascular free flap scalp reconstruction.Immediate free flap reconstruction over the site of GammaTile implantation did not result in any wound healing complications and did not compromise the viability of the transplanted tissue. This approach also provided immediate and localized radiation, possibly enhancing patient progression-free survival while reducing the likelihood of radiation-induced adverse effects.We report the first case of GammaTile implantation with immediate reconstruction of the overlaying soft tissue defect with a free flap. Despite the immediate local radiation produced by the tiles abutting the deep surface of the free flap, there were no complications noted in the vascularity of the transplanted tissue. This finding provides preliminary evidence supporting the safety of using free tissue transfer alongside GammaTile implantation for complex reconstruction.
Keywords: Glioblastoma multiforme; GammaTile therapy; microvascular free flap; Multidisciplinary management; recurrent brain tumor; scalp reconstruction; brachytherapy; oncologic integration; tissue viability